Distinct profiles of cerebral oxygenation in focal vs. secondarily generalized EEG seizures in children undergoing cardiac surgery - Lin, Rouyi; Du, Na; Ning, Shuyao; Zhang, Mingjie; Feng, Jinqing; Chen, Xinxin; Ma, Li; Li, Jia (Frontiers in Neurology, 2024)
Objectives: Seizures are common in children undergoing cardiopulmonary bypass (CPB). Cerebral oxygen saturation (ScO2) by near-infrared spectroscopy is routinely monitored in many centers, but the relations between the levels and changes of ScO2 and brain injuries remain incompletely understood. We aimed to analyze the postoperative profiles of ScO2 and cerebral blood flow velocity in different types of EEG seizures in relation to brain injuries on MRI. Methods: We monitored continuous EEG and ScO2 in 337 children during the first 48 hours after CPB, which were analyzed in 3-hour periods. Cerebral blood flow peak systolic velocity (PSV) in the middle cerebral artery was measured daily by transcranial Doppler. Postoperative cerebral MRI was performed before hospital discharge. Results: Based on the occurrence and spreading types of seizures, patients were divided into three groups as patients without seizures (Group N; n=309), those with focal seizures (Group F; n=13), or with secondarily generalized seizures (Group G; n=15). There were no significant differences in the onset time and duration of seizures and incidence of status epilepticus between the two seizures groups (Ps≥0.27). ScO2 increased significantly faster across Group N, Group G, and Group F during the 48 hours (P<0.0001) but its overall levels were not significantly different among the three groups (P=0.30). PSV was significantly lower (P=0.003) but increased significantly faster (P=0.0003) across Group N, Group G, and Group F. Group F had the most severe brain injuries and the highest incidence of white matter injuries on MRI among the three groups (Ps≤0.002). Conclusions: Postoperative cerebral oxygenation showed distinct profiles in secondarily generalized and particularly focal types of EEG seizures in children after CPB. A state of ‘overshooting’ ScO2 with persistently low PSV was more frequently seen in those with focal seizures and more severe brain injury. Information from this study may have important clinical implications in detecting brain injuries when monitoring cerebral oxygenation in this vulnerable group of children after CPB.